Political Leadership Transmission Practices by The Political Parties from 2006: A Study of Democracy in Bangladesh - Ruhullah, Mohammad Eisa; Purwaningsih, Titin (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The researcher aimed to study the democratic process of the practices of the political parties of Bangladesh on Power Transmission since 2006. The study applied the qualitative descriptive method. This article aimed to measure the democratic process, power transmission, and the systematic crisis of the political parties with their wings. The investigation found that the practices of the parties are not purely democratic since the independence of the country. The government is mostly entitled by the two significant parties though there is a showcase of democratic elections. The election commission is responsible for the fair election, but unfortunately, that is not independent at all. Moreover, the most significant issue is the distrust amongst authorities. That is why there are constitutional changes usually happen due to dishonesty under the dominant party. The Study refers to the amendment of the 15th constitutional practice, making the election system unfair because the election was happening while the current government still controls the systems. It makes the opposition not to trust in the election commission. Thus, the country needs to have a non-dominant electoral mechanism and back to the amendment of the 13th old practices to make sure the democracy and transparency of the leadership in the country by the fair election. Furthermore, it will ensure the stability and the commitment of all bureaucrats to fulfill their services properly without any kind of influence.